Microglia in invertebrate ganglia. - Sonetti, D (1994)
The results of this study lend strong support to the concept of the existence in insects and molluscs of a distinctive class of neuroglial cells comparable to vertebrate microglia. The evidence presented is as valid as that used in reference to the separate status of vertebrate microglia--i.e., the demonstration of a close structural and functional relationship of these cells with cells of the immune system. As in vertebrates, the excision of ganglia from three invertebrate species (the molluscs Planorbarius corneus and Mytilus edulis and the insect Leucophaea maderae) and their maintenance in incubation media led to an exodus of small cells and their accumulation in the culture dish. During this process, they underwent conformational changes from stellate to rounded, and then to more or less ameboid, comparable to those indicative of the process of activation in the animals' immunocytes. Functional characteristics which these translocated microglia-like cells share with immunocytes are motility, phagocytotic activity, and adherence to the culture dish. Furthermore, the two cells have certain biochemical features in common--e.g., the presence of certain cytokines and (at least in Planorbarius) that of corticotropin. An additional phenomenon of particular interest for the classification of microglial elements is their response to morphine. At 10(-6) M, this drug decreases not only the number of cells emerging from the excised ganglia but also the degree of their transformation to the "active" ameboid form. This dose-dependent and naloxone-sensitive effect of morphine on microglial cells parallels that on activated immunocytes of the same species. Corresponding results demonstrating an inhibitory effect of morphine on mobilized microglial cells of the frog Rana pipiens indicate that this relationship between the two cell types under consideration also exists in vertebrates. Binding and displacement experiments with membrane homogenates of microglial cells as well as immunocytes of Mytilus have shown that the effects of morphine on both cell types are mediated by the same special opiate receptor (mu 3).